Seismic performance of a narrow flange H-beam-to-column full-bolt end-plate weak-axis connection. (December 2022) - Zhong, Wei-hui; Zhao, Meng-jun; Zhou, Li; Tan, Zheng; Sun, Wei; Zheng, Yu-hui
Abstract: This study proposes a full-bolted end-plate weak-axis connection T-shape joint based on a narrow flange H-beam-to-column section. A quasi-static test was conducted to solve the problems of large steel cross-section and high steel utilization, as well as the decline in space utilization and aesthetics caused by convex beam-to-column components in low-rise and multi-story steel frame residential buildings. The failure mode, hysteresis curve, and bearing capacity of the specimens were discussed and investigated. The test results show that the stiffness of the joints of the specimens are relatively high, the failure mode is the beam hinge failure mechanism, the hysteresis curves of the joints are full fusiform, and the seismic performance is good. An experimental numerical model was established using the ABAQUS software to determine the factors that affect the performance of the joint. The effects of skin thickness, bolt diameter, beam end-plate thickness, stiffener thickness and rid slope on the seismic performance of the T-shape joint were analyzed. The numerical simulation results indicate that when the thickness of the skin plate increases, the energy dissipation capacity of the joint significantly increases, whereas the ductility decreases. a moment–rotation formula that can be used as a reference in the control design of the key parameters of the joint was obtained, which is useful in practical engineering applications.